The characteristics of the endometrial pathology in premenopausal period - F. T. Aliyeva; D. V. Bryunin (Лечащий Врач, 2023)
The goal of study was to study the incidence and the clinical manifestation of the endometrial pathology in premenopausal period. 73 premenopausal women with various endometrial pathology were examined. The average age of the examined was 47.82 ± 0.27 (45-51) years. The age of the menarche was 11.0 ± 0.15 (11-17) years, with the duration of the menstrual cycle 27.24 ± 0.47 (21-45) days and menstruation 5.1 ± 0.14 (3-8) grays. Onset of sexual activity was at age 19.5 ± 0.57 (16-31) years. The number of pregnancies was 5.2 ± 0.02 (1-10), from which 1.72 ± 0.11 (1-4) terminated with vaginal births, 1.57 ± 0.11 (1-4) with medical abortions, and 1.91 ± 0.34 (1-4) with spontaneous abortions. All the patients were conducted clinical, functional, hormonal, endoscopic, morphological methods of examination. The results obtained were subjected to statistical processing using standard computer programs "Statgraph", designed for parametric and non-parametric methods for calculating average values. There was confirmed that 5.5% of patients with various pathology of the endometrium had no clinical symptoms. 44.9% of examined had polymenorrhea, 29% menorrhagia, 21.7% metrorrhagia, 20.3% opsomenorrhea, 17.4% bloody spotting from the vagina, 17.4% of patients had lower abdominal pain and 13% had proyomenorrhea. Among the types of the endometrial pathology in the premenopausal period there was prevalence in the endometrial polyp, in 54.8% of patients (at the same time, a glandular-fibrous polyp of the endometrium was diagnosed in 45.2% of patients). 22.5% of examined had endometrial hyperplasia, 13% endometritis, and 9.6% combination of uterine Myoma and endometrial hyperplasia. The incidence of high grade endometrial cancer was 2.7%. Thus, in women with endometrial pathology, who are in the is a fairly high frequency of menstrual irregularities in combination with uterine pathology, which requires dynamic monitoring to prevent the development of complications and malignant neoplasms.premenopausal period, there  is a fairly high frequency of menstrual irregularities in combination with uterine pathology, which requires dynamic monitoring to prevent the development of complications and malignant neoplasms.